2013
DOI: 10.1111/1756-185x.12075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imatinib mesylate on pulmonary allergic vasculitis in a murine model

Abstract: ObjectivesImatinib mesylate (IM) is a potent and specific tyrosine inhibitor and has been reported to inhibit mesenchymal cell proliferation in pulmonary fibrosis. In the present study, we examine the effects of IM on vascular remodeling in a murine model of allergic vasculitis with eosinophil infiltration.MethodsC57BL/6 mice were sensitized with ovalbumin (OVA) and alum. The positive controls were exposed to aerosolized OVA daily for 7 days. IM treated mice with exposure to OVA were administered IM in paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…TGF-β not only promotes the proliferation and activation of myofibroblasts but also induces the exaggerated deposition of the extracellular matrix-including collagen and fibronectin in fibrotic tissues [32,33]. We previously reported a marked increase in TGF-β concentration in the BALF of OVA-sensitized mice after OVA exposure [34]. The present study demonstrated that tofacitinib decreased TGF-β concentration in the BALF of the OVA-sensitized mice after OVA exposure, and attenuated vascular remodeling of the pulmonary artery and the proliferation of myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β not only promotes the proliferation and activation of myofibroblasts but also induces the exaggerated deposition of the extracellular matrix-including collagen and fibronectin in fibrotic tissues [32,33]. We previously reported a marked increase in TGF-β concentration in the BALF of OVA-sensitized mice after OVA exposure [34]. The present study demonstrated that tofacitinib decreased TGF-β concentration in the BALF of the OVA-sensitized mice after OVA exposure, and attenuated vascular remodeling of the pulmonary artery and the proliferation of myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Amin et al () reported that the number of mast cells was increased at sites of allergic inflammation of patients with atopic and nonatopic asthma. Suzuki et al () and Wambre et al () reported that Ki67‐expressing cells were increased in a mouse model of pulmonary allergic vasculitis and in pollen‐allergic individuals. Okayama & Kawakami () suggested that pharmacologic intervention for a decrease in the proliferation of mast cells could be a strategy for regulation of allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Выявлены также дозозависимый протекторный и противовоспалительный эффекты иматиниба при аутоиммунном повреждении легких у мышей [2]. Блокирование острого воспаления показано при аллергическом васкулите с эозинофильной инфильтрацией [11] и аутоиммунном артрите [12]. На модели индуцированного коллагеном артрита иматиниб продемонстрировал способность в микромолярной концентрации блокировать сигнальные пути активации тучных c-Kit + -клеток и высвобождение ФНО-α, цитокиновую продукцию и пролиферацию клеток.…”
unclassified